Optimisation of fat reduction in Jelawat (Leptobarbus Hoevenii) by garlic extract using resronse surface methodology (RSM) / Nor Addawiyyah Che Mohamad - Che Mohamad, Nor Addawiyyah (Faculty of Applied Sciences, 2008)
Garlic-rich organosulfur compounds and their precursors (allicin, diallyl sulfide and diallyl trisulfide) are believed to play a key role in these biological effects. Garlic may decrease triglyceride and cholesterol levels in patients with decrease levels of lipids. Allicin reduces serum cholesterol and triglyceride levels as well as atherosclerotic plaque formation, prevents platelet aggregation and decreases blood pressure. The antimicrobial, antitumor, antifungal, and inhibitory immunomodulatory activities of allicin have been reported. The jelawat (Leptobarbus hoevenii) was chosen as a sample because Jelawat contains 16.7% fat. It was categories as high fat fish. Optimisation of various parameters using response surface methodology (RSM) was performed to reduce the fat content in jelawat. MINITAB software version 14 was used to identify the significant effect of various parameters such as concentration of garlic extract, temperature and time immersion. Among the three variables tested, concentration of garlic and temperature immersion were found to have significant reduce fat. The fat content in jelawat was optimally reduced by 90.50% when it was treated with garlic at the optimum condition at concentration of garlic extract 14.56% at the temperature 56.8°C for 46.8 minutes.